KAJIAN SIFAT KIMIA TANAH DELTA MAHAKAMKABUPATEN KUTAI KARTANEGARA - Desiana - (PROSIDING SEMINAR KIMIA, 2014)
Research was aim to know so me of soil chemical propert ies in Delta Mahakam Kutai Kartanegara District. Research was conducted for three months in five different locations to representatives of the Mahakam Delta. Each of the sites were taken soil sample by drilling as many as 10 points at a depth of 0 -20 cm, 20-40 cm and 40-60 cm. Furthermore, fro m all of the 10 points were co mposite and taken 1 kg were performed at each depth. Soil samples were analy zed in the laboratory to be analyzed conditions: pH, organic C, C / N ratio, total N, availab le P, available K, and pyrite. Determination of soil chemical status was based on the chemical properties of the soil assessment criteria made by the Centre for Soil Research, Bogor (1983) in Hard jowigeno (2003), and the status of pyrite was based on criteria made by Hardjo wigeno and Widiat maka (2001). Results of this study concluded that the chemical properties of the soil at several locations Mahakam Delta were varied fro m low to very h igh. Average soil react ion (pH) was moderately acid, phosphorus available was mediu m, potassium availab ility was very high and total nitrogen was med iu m, organic carbon was high, C / N ratio was high - and pyrite was safe / not dangerous.